KAJIAN TEORITIS TERHADAP AUXILIARY STATE`S ORGAN DALAM STRUKTUR KETATANEGARAAN INDONESIA - Ahmad Basarah (Masalah-Masalah Hukum, 2014)
The Amendment of Indonesia's Constitution has brought the implication to the change of Indonesia democracy's system, which can be seen in the structure of State's institutions. The State's structure had been added with newly organs which are not existed in a prior time and have been made as the subsidiary or the supporting ones. They have known as the Auxiliary State's Institutions or the Auxiliary State`s Organs which help the functions of the main organs. This paper will not analyze in legal postivism perspectives and the results are expected to provide the answers to the needs of those institutions